THEORETICAL FUNDAMENTALS OF STUDY PEN AND GENERAL PRINCIPLES OF DRAWING - Sadatov Chori Xolmurodovich; Qudratov Javli Xolbozorovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the depiction of the performance of the half-stature of an elderly resin man. The most important parts of the human body are the head, neck, shoulders, chest area of the body, pelvis, and upper and lower limbs. Before drawing their whole picture together, pay attention to the structure and shape of each of them, practice drawing separate quick sketches. The shapes of the human body are manifested in different personalities, many complex and unique combinations. It is the most complex object to draw a human figure. The shapes of the human body come in many different personalities, in many complex and varied combinations.